Glutathione-S-transferase FosA6 of klebsiella pneumoniae origin conferring fosfomycin resistance in ESBL-producing Escherichia coli - Guo, Q; Tomich, A; McElheny, C; Cooper, V; Stoesser, N; Wang, M; Sluis-Cremer, N; Doi, Y (Oxford University Press, 2016)
Objectives: The objectives of this study were to elucidate the genetic context of a novel plasmid-mediated fosA variant, fosA6, conferring fosfomycin resistance and to characterize the kinetic properties of FosA6. Methods: The genome of fosfomycin-resistant Escherichia coli strain YD786 was sequenced. Homologues of FosA6 were identified through BLAST searches. FosA6 and FosAST258 were purified and characterized using a steady-state kinetic approach. Inhibition of FosA activity was examined with sodium phosphonoformate. Results: Plasmid-encoded glutathione-S-transferase (GST) FosA6 conferring high-level fosfomycin resistance was identified in a CTX-M-2-producing E. coli clinical strain at a US hospital. fosA6 was carried on a self-conjugative, 69 kb IncFII plasmid. The ΔlysR-fosA6-ΔyjiR_1 fragment, located between IS10R and ΔIS26, was nearly identical to those on the chromosomes of some Klebsiella pneumoniae strains (MGH78578, PMK1 and KPPR1). FosA6 shared >99% identity with chromosomally encoded FosAPMK1 in K. pneumoniae of various STs and 98% identity with FosAST258, which is commonly found in K. pneumoniae clonal complex (CC) 258 including ST258. FosA6 and FosAST258 demonstrated robust GST activities that were comparable to each other. Sodium phosphonoformate, a GST inhibitor, reduced the fosfomycin MICs by 6- to 24-fold for K. pneumoniae and E. coli strains carrying fosA genes on the chromosomes and plasmids, respectively. Conclusions: FosA6, probably captured from the chromosome of K. pneumoniae, conferred high-level fosfomycin resistance in E. coli. FosA6 functioned as a GST and inactivated fosfomycin efficiently. K. pneumoniae may serve as a reservoir of fosfomycin resistance for E. coli.